2022
DOI: 10.1155/2022/4102666
|View full text |Cite|
|
Sign up to set email alerts
|

Homeobox A1 Facilitates Immune Escape and Alleviates Oxidative Stress in Lung Adenocarcinoma

Abstract: Objective. Recent studies have demonstrated that homeobox A1 (HOXA1) is upregulated in lung cancer due to RNA modifications (N6-methyladenosine), but the specific function of HOXA1 in lung adenocarcinoma (LUAD) remains indistinct. Herein, we investigated the role of HOXA1 in LUAD biology. Methods. This study presented pancancer analysis of associations of HOXA1 with prognosis, TMB, and immune checkpoints. The expression of HOXA1 was detected in LUAD and normal tissues with immunohistochemistry and western blot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…We found that high HOXA1 expression was associated with poor prognosis and high recurrence risk in HNSCC and LGG patients who had undergone postoperative radiotherapy, and in NPC patients who had undergone radical radiotherapy, whereas HOXA1 had no predictive value with respect to prognosis in patients who underwent surgery alone. Many studies have reported that elevated HOXA1 expression is correlated with poor prognosis in multiple cancer types (30,31). However, little was known about whether high HOXA1 expression promotes the radioresistance of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…We found that high HOXA1 expression was associated with poor prognosis and high recurrence risk in HNSCC and LGG patients who had undergone postoperative radiotherapy, and in NPC patients who had undergone radical radiotherapy, whereas HOXA1 had no predictive value with respect to prognosis in patients who underwent surgery alone. Many studies have reported that elevated HOXA1 expression is correlated with poor prognosis in multiple cancer types (30,31). However, little was known about whether high HOXA1 expression promotes the radioresistance of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated notable associations between HOXA1 and immune cell infiltration as well as immune checkpoints. Knockdown of HOXA1 in LUAD cells enhances the CD8 + T cell response [ 98 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported that HOX genes act as transcription factors, and these transcription products play key roles in the development of cancers 7 . HOXA family genes were identified as transcription factors that are involved in the development of various cancers, and have been reported to play important roles in TME 8,9 . Previous research has shown that HOXA7 is a member of the HOXA transcription factor family and was reported to play important roles in a number of malignancies including liver cancer, 10 colorectal cancer, 11 breast cancer, 12 and myeloid leukemia 13 .…”
Section: Introductionmentioning
confidence: 99%